Antibiofilm Efficacy and Mode of Action of Etlingera elatior Extracts Against Staphylococcus aureus - Hamdan, Hanis Fadhlina; Ross, Ernie Eileen Rizlan; Jalil, Mohd Taufiq Mat; Hashim, Mohd Akmal; Yahya, Mohd Fakharul Zaman Raja (Malaysian Applied Biology, 2024)
Staphylococcus aureus represents a major bacterial human pathogen that causes a wide variety of clinical manifestations. Various medicinal plants have been used to control its infection, however, the effect of Etlingera elatior on S. aureus biofilm is still uncertain. Thus, the objective of this study was to evaluate the antibacterial and antibiofilm efficacy of E. elatior extracts against S. aureus. Phytochemical screening was carried out to determine the presence of phenols, tannins, saponins, and alkaloids in different extracts (acetone, methanol, ethanol, and aqueous) of E. elatior. Antibacterial activities were determined by disk diffusion assay, minimum inhibitory concentration assay (MIC), and minimum bactericidal concentration assay (MBC) while antibiofilm activities were determined by crystal violet assay and Fourier-transform infrared (FTIR) spectroscopy. All the extracts were found to contain phenols, tannins, saponins, and alkaloids. Only acetone extract showed a high amount of saponins. Among all the extracts, acetone extract showed the widest inhibition zone (21.23±0.2 mm), lowest MIC (20 mg/mL), and lowest MBC (50 mg/mL) values. The acetone extract also showed the highest antibiofilm activities at all biofilm stages (6 hr: 12%-31%; 12 hr: 20%-36%; 18 hr: 27%-32%; 24 hr: 5%-46%). Further analysis with FTIR spectroscopy revealed spectral changes associated with proteins (1700–1400 cm-1), phospholipids, and polysaccharides (1300–700 cm-1) in S. aureus biofilm following the treatment with 200 mg/mL of E. elatior extracts. In conclusion, E. elatior is a potential source of antibacterial and antibiofilm agents to control S. aureus infections. Changes in the composition of proteins, phospholipids, and polysaccharides may mediate the biofilm inhibition by E. elatior extracts. The acetone extract of E. elatior may be useful for various applications such as antimicrobial topical cream and wound dressing.